FPGA-Based Real-Time Simulation of Dual-Port Submodule MMC–HVDC System - Zhao Jin; Yanjie Wu; Shuyuan Wang; Bingda Zhang (Energies, 2022)
Aiming at the problems of the high switch numbers, complex working mechanisms, and complicated real-time simulation of modular multilevel converters (MMCs) composed of dual-port submodules, in this study, we designed a unified equivalent model of the multiple submodule network by analyzing the combination of parallel submodules in the bridge arm. The proposed model decouples the submodules that do not affect each other in the subnetwork calculation process, thereby reducing the number of prestored parameters in the subnetwork simulation. In the Xilinx Virtex-7 FPGA VC709 (Xilinx Corporation, San Jose, CA, USA) development board, we replaced the inline computation combined with the prestorage of parameters with the proposed equivalent model to optimize the execution unit structure and redesigned the FPGA-Based Real-Time Digital Solver (FRTDS). Taking the P-FBSM-based MMC–HVDC system as the simulation object, we performed a real-time simulation with a step size of 10 μs, which verified the effectiveness of the proposed model and the improvement in the hardware. We compared the results with the offline MATLAB/Simulink simulation results to verify the accuracy of the simulation.